Rational design of multi-walled carbon nanotube@hollow Fe3O4@C coaxial nanotubes as long-cycle-life lithium ion battery anodes. (4th September 2019) - Shi, Xiuling; Yao, Qianqian; Wu, Hefeng; Zhao, Yi; Guan, Lunhui
Abstract: In this work, we report a high-performance anode material created by rationally encapsulating multi-walled carbon nanotubes (MWNTs) within hollow Fe3 O4 nanotubes followed by applying a carbon coating. When tested for lithium storage, as-prepared MWNT@hollow Fe3 O4 @C coaxial nanotubes present high specific capacity, superior rate performance, and outstanding cycling stability. It is capable of delivering high capacities of 758 mA h g −1 at 500th cycle at 0.2 A g −1, and 409 mA h g −1 after 1000 cycles at a high rate of 1.5 A g −1 . This excellent performance can be attributed to its unique architecture, which provides high electrical conductivity, offers enough void space for volume accommodation, and mitigates the pulverization of Fe3 O4 during cycles.